Heart Failure among People with HIV: Evolving Risks, Mechanisms, and Preventive Considerations - Toribio, Mabel (Curr HIV/AIDS Rep, 2019)
PURPOSE: People with HIV (PHIV) with access to modern antiretroviral therapy (ART) face a two-fold increased risk of heart failure as compared to non-HIV-infected individuals. The purpose of this review is to consider evolving risks, mechanisms, and preventive considerations pertaining to heart failure among PHIV. RECENT FINDINGS: While unchecked HIV/AIDS has been documented to precipitate heart failure characterized by overtly reduced cardiac contractile function, ART-treated HIV may be associated with either heart failure with reduced ejection fraction (HFrEF) or with heart failure with preserved ejection fraction (HFpEF). In HFpEF, a “stiff” left ventricle cannot adequately relax in diastole – a condition known as diastolic dysfunction. Diastolic dysfunction, in turn, may result from processes including myocardial fibrosis (triggered by hypertension and/or immune activation/inflammation) and/or myocardial steatosis (triggered by metabolic dysregulation). Notably, hypertension, systemic immune activation, and metabolic dysregulation are all common conditions among even those PHIV who are well-treated with ART. Of clinical consequence, HFpEF is uniquely intransigent to conventional medical therapies and portends high morbidity and mortality. However, diastolic dysfunction is reversible – as are contributing processes of myocardial fibrosis and myocardial steatosis. SUMMARY: Our challenges in preserving myocardial health among PHIV are two-fold. First, we must continue work to realize UNAIDS 90–90-90 goals. This achievement will reduce AIDS-related mortality, including cardiovascular deaths from AIDS-associated heart failure. Second, we must work to elucidate the detailed mechanisms continuing to predispose ART-treated PHIV to heart failure and particularly HFpEF. Such efforts will enable the development and implementation of targeted preventive strategies.